Astragaloside IV attenuates sunitinib-associated cardiotoxicity by inhibiting COUP-TFII - Wanting Qin; Shaoling Li; Ziji Cheng; Wenlong Xue; Mingyue Tian; Fangfang Mou; Haidong Guo; Shuijin Shao; Baonian Liu (Heliyon, 2024)
Sunitinib (SU) is widely used to treat solid tumors but it can be cardiotoxic and often leads to drug withdrawn or discontinuation. Astragaloside IV (ASIV) is the essential active component of the Chinese herb Astragalus membranaceus which shows potential cardioprotective effects. Herein, we investigated the effect of ASIV on SU-associated cardiotoxicity and its mechanisms. We showed that ASIV significantly ameliorated SU-induced myocardial injury in mice, as evidenced by an improvement in left ventricular ejection fraction (EF) and a decrease in blood pressure and serum concentration of myocardial injury markers. ASIV attenuated SU-induced myocardial inflammatory infiltration and fibrotic lesions. In addition, ASIV suppressed SU-induced myocardial oxidative stress and apoptosis both in vitro and in vivo. Furthermore, SU increased COUP-TFII expression both in mRNA and protein levels in mice myocardial tissue, primary neonatal rat cardiomyocytes (NRCMs) and H9c2 cell lines, and this effect was rescued by ASIV. Knockdown of COUP-TFII reduced the oxidative stress and apoptosis induced by SU in NRCMs and H9c2 cell lines. However, the overexpression of COUP-TFII blocked the protective effects of ASIV on SU-treated cardiomyocytes. Thus, our results demonstrated that ASIV ameliorated SU-indued cardiotoxicity by inhibiting COUP-TFII, suggesting that ASIV might be a potential therapeutic strategy for the prevention of SU-associated cardiotoxicity.